P1-41. Verification of stimulation site in bulbocavernous reflex (BCR) monitoring. Issue 9 (September 2017) - Sugiyama, Kunio; Ando, Shunpei; Masuda, Hiroyuki; Kondo, Kosuke; Wada, Akihito; Harada, Naoyuki; Nemoto, Masaaki; Takahashi, Hiroshi; Sugo, Nobuo
Abstract : Bulbocavernosus reflex (BCR) monitoring is useful for lumbar and cauda surgery. However, in some cases BCR may be difficult to record. We report verification of the stimulation site of BCR monitoring. The subjects were 24 patients undergoing BCR monitoring from 2010 to 2015 (0–79 years old, 14 males, 10 females). In all cases, BCR was recorded from the needle electrode of the anal sphincter. An adult male stimulated the dorsal side of the penis. The boy stimulated the dorsal and ventral side of the penis. Women were classified into three types: clitoral and labia stimulation, left and right side stimulation of the clitoris, clitoris and pubis stimulation. An adult male was able to record in all cases. An adult female could record with a type that stimulated the clitoris and labia. Childhood cases were difficult to record in all cases. Women's BCR stimulation needs to directly stimulate the clitoris. Children may be involved in neuropathy due to congenital diseases or underdeveloped nerve.